Experimentally determined distribution of granular-flow characteristics in collisional bed load transport - Matoušek Václav; Zrostlík Štěpán; Fraccarollo Luigi; Prati Anna; Larcher Michele (EPJ Web of Conferences, 2018)
A series of laboratory experiments on turbulent open-channel two-phase flow in a form of intense bed load transport is reported. Measurements in a laboratory tilting flume included camera based imaging techniques to identify the structure of the flow at the local level. Obtained experimental distributions of two-phase flow related parameters - granular velocity, concentration, and temperature - across a collisional transport layer are discussed. The results are analysed together with additional measured quantities (discharges of mixture and grains, flow depth, bed slope etc). Our major goal is to evaluate the distribution of granular stresses across the transport layer with a special attention paid to the interface between the transport layer and the bed. Furthermore, comparisons are discussed between the experimental results and predictions produced by suitable kinetic-theory based models.